Factors influencing intention to purchase fraudulent honey among Malaysian consumers - Ahmad, Nur Nisaa (2021)
This study explores the topic of food fraud using honey as the context. Honey has been identified statistically as one of the most adulterated ingredients. It has a long history of dilution, substitution, misrepresentation of floral source, and geographical origin. The fraudulent honey industry has caused millions of dollars lost among pure honey producers around the world. But more alarmingly, the nutritional contents have been jeopardised by the fraudsters, which has resulted in consumers suffering monetary loss and exposed to health hazards. Gullible consumers create convenient targets for motivated offenders to take advantage of. Ignorance in consumers leads to poor buying practices. Our central thesis is that awareness influences the consumers' purchase intention, which later dictates their purchasing decision. Ideally, increasing awareness about honey fraud would minimise the purchase of fraudulent honey, hence encouraging fair competition among traders and eventually reducing the supply of fraudulent honey. Given the limited research on this topic, this paper aims to assess consumer awareness about fraudulent honey and its impact on purchase intention using an extended Theory of Planned Behaviour model. A quantitative online questionnaire survey was administered among Malaysian honey consumers. Multiple regression analysis was employed to generate the relationship between awareness, attitude, subjective norms, perceived behavioural control, and consumers' intention to purchase fraudulent honey. Findings show that consumers are aware of fraudulent honey but choose to buy it. Attitude and perceived behavioural control have a significant and positive relationship with the intention to purchase fraudulent honey. Consumers' unfavourable attitude towards fraudulent honey diminishes their intention to purchase it. Whereas, even with high perceived behavioural control, consumers choose to purchase fraudulent honey because it fulfils their needs. This study's practical implication is for marketers and policymakers to develop programs or create proper channels to educate consumers in making wise purchasing decisions.